Breaking Business as Usual : Fostering Competitiveness and a Dynamic Environment for Private Sector Growth - Schneider, Charles (World Bank, Yangon, 2016)
Market-based reforms and the opening up of trade and investment initiated over the past four years have had a positive impact on growth in Myanmar. These have enhanced private sector participation and increased the role of exports in the economy. Reforms have included streamlined business entry procedures, reduced export and import licensing requirements, and enhanced public-private partnerships and dialogue. Promoting private sector competitiveness and inclusion in Myanmar have enormous potential to drive job creation, economic diversification, and structural transformation. This would involve improving the investment climate with an emphasis on transparency and predictability; reducing trade costs and strengthening connectivity for economic integration; enhancing public-private partnerships; and strengthening institutional capacity to drive the reform process. The ongoing peace process calls for careful sequencing of reforms, starting with reducing the costs of doing business and engaging in trade; consulting with local communities; and supporting vulnerable groups adversely affected by economic changes.